Perbandingan Hasil Skrining Fitokimia Daun Melinjo (Gnetum gnemon L.) Dengan Metode Maserasi Dan Sokhletasi - Sholikhah Deti Andasari; Alfia Amalia Hermanto; Astri Wahyuningsih (Universitas Muhammadiyah Klaten, 2020)
Melinjo leaves have many benefits because they contain quite complex secondary metabolites. The purpose of this study was to determine the comparison of the results of phytochemical screening on melinjo leaves using maceration and sokletation methods. This research is a descriptive qualitative research conducted using several reagents, which are adjusted to the type of phytochemical test (flavonoids, alkaloids, saponins and tannins). The research stages included sample preparation, extraction process, and phytochemical screening. The results of phytochemical screening on melinjo leaves showed that the maceration and sokhletation extraction processes contained flavonoids, alkaloids, saponins and tannins. The difference that occurs is that in the saponin compounds, the results show that the foam in the macerated extract is more than in the soxhletation extract. The conclusion of this study shows that the extract of melinjo leaves contains flavonoids, alkaloids, saponins, and tannins.